Inspiring mathematics and science in teacher education : final report. - Goos, Merrilyn; Grotowski, Joseph; Bennison, Anne (Australia, Dept of Education and Training, 2017)
Final report from a project that promoted strategic change in the Australian higher education sector by developing and disseminating new interdisciplinary approaches to mathematics and science pre-service teacher education. This was achieved by fostering genuine and sustained collaboration between mathematics, science, and education scholars so as to institutionalise new ways to integrate their collective content and pedagogical expertise. The project generated a coherent suite of teacher education strategies that were tested in a range of institutional contexts within the lead and partner universities, and widely disseminated through systematic engagement with universities outside the project team.